Ultra wideband wireless communication (Wiley-Interscience, 2006)
Focusing on ultra wideband (UWB) communication technology for applications including WPAN, sensor and ad-hoc networks, as well as wireless telemetry and telemedicine, Ultra Wideband Wireless Communication covers both theory and practical issues, including RF, hardware and circuit issues and digital signal processing aspects.